Perceptions of Self, Power, & Gender Among Muslim Women Narratives from a Rural Community in Bangladesh - Alam, Sarwar (Springer International Publishing, 2018)
This book analyzes perceptions of self, power, agency, and gender of Muslim women in a rural community of Bangladesh. Rural women's limited power and agency has been subsumed within the male dominated Islamic discourses on gender. However, many Muslim women have their own alternative discourses surrounding power and agency. Sarwar Alam intertwines an exploration of these power dynamics with reading of the Qur'an and Hadith, and analyzes how Muslim women's perception of power and gender are linked to their relationship with religion.